Promotion Incentives in the Public Sector: Evidence from Chinese Schools - Naureen Karachiwalla; Albert Park (Institute of Labor Economics (IZA), 2017)
We provide evidence that promotion incentives influence the effort of public employees by studying China's system of promotions for teachers. Predictions from a tournament model of promotion are tested using retrospective panel data on primary and middle school teachers. Consistent with theory, high wage increases for promotion are associated with better performance, teachers increase effort in years leading up to promotion eligibility, and reduce effort if they are repeatedly passed over for promotion. Evaluation scores are positively associated with teacher time use and with student test scores, diminishing concerns that evaluations are manipulated.
Keywords: J31; J33; J45; M51; 330; teacher incentives; promotions; China